2020
DOI: 10.5507/bp.2019.041
|View full text |Cite
|
Sign up to set email alerts
|

Chronic calcified subdural hematoma - case report of a rare diagnosis

Abstract: Introduction. Chronic calcified/ossified subdural hematoma is a rare diagnosis. The incidence of chronic calcified subdural hematoma is 0.3-2.7% of all chronic subdural hematomas. Surgical treatment is indicated in most cases, but there is still some controversy. Materials and Methods. We present a case report of 81-year-old woman with calcified chronic subdural hematoma. Patient underwent an osteoplastic left craniotomy, evacuation of chronic subdural mass with careful dissection andsuccessful removal of inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Calcified subdural hematoma has been described as a case report. Around 114 case reports have been described in the literature [1][2][3][4][5][6][7][8]. As per a systematic review of 114 cases reported in the literature, it has been found that the incidence of CSDH is high in certain countries, including the United States, Japan, and Turkey, with a steady increase in recent years [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcified subdural hematoma has been described as a case report. Around 114 case reports have been described in the literature [1][2][3][4][5][6][7][8]. As per a systematic review of 114 cases reported in the literature, it has been found that the incidence of CSDH is high in certain countries, including the United States, Japan, and Turkey, with a steady increase in recent years [8].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, all symptoms are almost the same as those of non-calcified CSDH. Most of the case reports have been described in children and the elderly [3][4][5][6][7]. In chronic cases of subdural hematoma (SDH), the incidence of calcification is much higher, and all symptomatic CSDH should be treated surgically [7].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic subdural hematoma is not uncommon; however, calcified chronic subdural hematoma is extremely uncommon with an incidence about 0.3–2.7% of all cases of chronic subdural hematoma [ 1 ]. Generally, the conditions have more affected children than adults [ 2 ], but in this presentation, we presented this rare condition in an elderly patient.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification of chronic subdural hematoma is an extremely rare condition. The incidence is about 0.3–2.7% of all chronic subdural hematoma [ 1 ]. The lesion most commonly occurred in children [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kronik kalsifiye subdural hematom insidansı, tüm kronik subdural hematomların %0,3-2,7'sidir. 2 Türk Ceza Kanunu'nun (TCK) 86, 87 ve 89. maddelerinde de belirtildiği gibi ceza kanunumuz yaralama suçlarında faile verilecek cezanın oranını be-…”
unclassified